Exosomes: A Novel Biomarker and Approach to Gene Therapy for Spinal Muscular Atrophy - Nash, Leslie (Université d'Ottawa / University of Ottawa, 2019)
Spinal muscular atrophy (SMA) is a neuromuscular disease caused by reduced levels of the survival motor neuron (SMN) protein. SMA results in degeneration of motor neurons, progressive muscle atrophy, and death in severe forms of the disease. Currently, there is a lack of inexpensive, readily accessible, accurate biomarkers to study the disease. Furthermore, the current FDA approved therapeutic is neither 100 % effective nor accessible for all patients, thus more research is required. Tiny cell derived vesicles known as exosomes have been evaluated in an attempt to identify novel biomarkers for many disease states and have also shown therapeutic promise through their ability to deliver protein and nucleic acid to recipient cells. The research presented herein investigates whether (1) the level of SMN protein in exosomes isolated from the medium of cells, and serum from animal models and patients of SMA is indicative of disease, to serve as a biomarker for monitoring disease progression and therapeutic efficacy; (2) SMN-protein loaded exosomes can be utilized to deliver SMN protein to SMN-deficient cells; (3) adenoviral vectors are effective at creating SMN protein-loaded exosomes in situ for body wide distribution of SMN protein. This research has shown SMN protein is naturally released in extracellular vesicles, and the level of exosomal SMN protein is reflective of the disease state. Exosomes can also be modified to hold enhanced levels of SMN protein and deliver them to both the cytoplasm and nucleus of SMN-deficient cells. Furthermore, adenoviral vectors expressing luciferase-tagged SMN1 cDNA, targeted to the liver, results in SMN protein-loaded exosomes and detectable luciferase activity, body-wide. Thus, exosomes present as an effective biomarker and potentially a novel approach to treat SMA.
Keywords: Spinal muscular atrophy; Gene therapy; Adenovirus; Exosomes; Biomarker; Neuromuscular; Adenoviral vector; Survival motor neuron; Motor neuron; protein therapy